9 - Note sur l’Evolution de la Structure du Financement Extérieur de l’Afrique Sub-Saharienne - René Nguettia Kouassi (Africa Development, 1991)
This study analyzes the international financing of development and its consequent effects on the economies of the recipient countries. In particular , it deals with the evolution of the external financing structure of the countries of Sub-Saharan Africa and draws the following conclusions : the stagnation of Official Development Assistance (ODA) has led to the increase of public or private loans that have restrictive terms of payment attached. There is a tendency for ODA to be concentrated in the poorer countries , whereas the loans conditioned by the international market are directed towards the richer countries , especially those that are considered more solvent; at present, the external financing structure is too encumbered and inequitable for the recipient countries. As a result , several of these countries have been sinking lower into debt during the past few years. This now raises the question as to the type of financing to be accorded to these countries; should the former external financing structure be restored or should the new structure be modified and maintained? from the standpoint of the recipient countries , the former financing structure may contain elements that could partially resolve the difficulties they are facing.